Constitutional Law Health: Class Medical View on the Outsourcing of Public Health in Santos/SP City - Alexandre Ricardo Machado; Juliana Buck Gianini (Revista de Direito Administrativo e Gestão Pública, 2015)
Faced with growing globalization of the new administrative concepts are created seeking efficiency and economy in public services, ariese to outsourcing in the Brazilian public health. This model has grown significantly, with the creation of Social Organizations - OSs. Due to the relevance of the topic, it was formulated the following problem: the constitutional right to health is treated in prestacional context and what is the medical profession insight into the outsourcing of public health in the city of Santos/SP. The present study was justified given the increasing intensification of outsourcing in the Brazilian health. The study objectives this verify the legality and viability of outsourcing, as the choice of OSs in the provision of public health services (SUS) and what the views of key stakeholder, the doctor, who has direct contact with the type of service. The methodology was based on two analyzes: (i) bibliographic search, using descriptive research as a means of response to your goal, through legislation, doctrine and jurisprudence; (ii) field research based on case study by applying questionnaires to doctors and managers / Public former managers of the city of Santos/SP.